Two complementing in vivo selection systems based on CCA-trimming exonucleases as a tool to monitor, select and evaluate enzymatic features of tRNA nucleotidyltransferases - Karolin Wellner; Josefine Gnauck; Dorian Bernier; Stephan H. Bernhart; Heike Betat; Mario Mörl (RNA Biology)
tRNA nucleotidyltransferase represents a ubiquitous and essential activity that adds the indispensable CCA triplet to the 3’-end of tRNAs. To fulfill this function, the enzyme contains a set of highly conserved motifs whose coordinated interplay is crucial for the sequence-specific CCA polymerization. In the human enzyme, alterations within these regions have been shown to lead to the manifestation of disease. Recently, we developed an in vivo screening system that allows for the selection and analysis of tRNA nucleotidyltransferase variants by challenging terminal AMP incorporation into tRNA during induced RNase T-catalyzed CCA-decay. Here, we extend this method for screening of full CCA-end repair by utilizing the CCA-trimming activity of exonuclease LCCR4. To demonstrate the combined potential of these two in vivo selection systems, we applied a semi-rational library design to investigate the mode of operation of catalytically important motifs in the human CCA-adding enzyme. This approach revealed unexpected requirements for amino acid composition in two motifs and gives new insights into the mechanism of CCA addition. The data show the potential of these RNase-based screening systems, as they allow the detection of enzyme variations that would not have been identified by a conventional rational approach. Furthermore, the combination of both RNase T and LCCR4 systems can be used to investigate and dissect the effects of pathogenic mutations on C- and A-addition.